Examining the Effects of Celebrity (Vs. Noncelebrity) Narratives on Opioid Addiction Prevention: Identification, Transportation, and the Moderating Role of Personal Relevance. Issue 5 (4th May 2022) - Vafeiadis, Michail; Wang, Weirui; Baker, Michelle; Shen, Fuyuan
Abstract : Celebrity disclosures and narratives are popular strategies in health promotion. However, less is known about their joint effects and the mechanisms through which they function. A 2 ( narrative type : celebrity vs. layperson) x 2 ( personal relevance : low vs. high) online experiment (N = 248) tested the impact of different narrative types in increasing awareness about prescription opioid abuse. Results indicated that a celebrity narrative is more persuasive than its layperson counterpart. Also, personal relevance toward opioid addiction moderated the influence of narrative type. Celebrity narratives evoked more positive attitudes toward opioid prevention and greater behavioral compliance intentions with the recommended action for low-relevance individuals. Transportation and identification mediated the effects of celebrity narratives on participants' issue attitudes and behavioral intentions, but only for low-relevance individuals. Practically, the data suggest that incorporating celebrities in health narratives about opioid addiction prevention facilitates behavioral compliance, especially for individuals to whom a pressing health issue like opioid misuse is currently of low relevance.